Universal design approach for the children with physical disabilities: a study in mainstream primary schools, Naogaon district, Bangladesh - Hossain, Zaman; Abdul Rahim, Asiah (Noor Publishing, 2019)
The objectives of this study are firstly to understand how the parents and the primary schools are handling Children with Physical Disabilities (CwPDs), secondly to identify the challenges faced by the CwPDs particularly during school hours and thirdly the application of Universal Design Guidelines (UDG) suitable to mainstream primary school is also a significant aspect of this study. The study highlighted the need for barrier-free access for the CwPDs. This research is conducted in one of the 64 districts (Naogaon) in Bangladesh. The methodology is based on access audit checklists, case studies, observations and interviews of the CwPDs and their parents. The findings from the 38 case studies which indicate the need for understanding multi-dimensional factors such as lack of awareness among people and authority in providing facilities for the CwPDs. It is evident from the access audit checklist that the provision of accessible features like pathways, main entrances, ramps, corridors, toilets, had not to be made to fulfil the needs of CwPDs and the compliance towards UDG for accessible design is not being applied in general.